2014
DOI: 10.1016/j.vaccine.2014.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing benefits of influenza virus vaccination during pregnancy: Potential behavioral risk factors and interventions

Abstract: Pregnant women and infants are at high risk for complications, hospitalization, and death due to influenza. It is well-established that influenza vaccination during pregnancy reduces rates and severity of illness in women overall. Maternal vaccination also confers antibody protection to infants via both transplacental transfer and breast milk. However, as in the general population, a relatively high proportion of pregnant women and their infants do not achieve protective antibody levels against influenza virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 113 publications
1
6
0
Order By: Relevance
“…In short, our results consistently confirm those obtained by other groups [1, 27, 35], where more than half of vaccination rejections stemmed from a perceived lack of data on the efficacy and safety of vaccine. Due to the determinant influence of these perceptions and beliefs, it is essential to carry out qualitative studies that would inform and facilitate improvement interventions.…”
Section: Discussionsupporting
confidence: 91%
“…In short, our results consistently confirm those obtained by other groups [1, 27, 35], where more than half of vaccination rejections stemmed from a perceived lack of data on the efficacy and safety of vaccine. Due to the determinant influence of these perceptions and beliefs, it is essential to carry out qualitative studies that would inform and facilitate improvement interventions.…”
Section: Discussionsupporting
confidence: 91%
“…The protective effects of regular physical exercise on these infectious diseases may be partially explained by enhanced activity of several immune parameters that could be important in limiting or clearing viral infection [ 11 ]. In addition, numerous studies have revealed that behavioral interventions, particularly those focused on exercise, can enhance antibody responses to vaccination [ 12 13 ]. This suggests that exercise is an appealing behavioral intervention for infectious disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between hormones and immune mediators in systemic circulation and at the mother-fetal interface alter influenza pathogenesis in the pregnant host, as well as contribute to sex-based differences in the response to infection (Irving et al 2000;Raj et al 2014;van Riel et al 2016;Littauer and Skountzou 2018). Other comorbidities, including stress, depression, body mass index, aging, puberty, and exercise state, contribute to poor infection responses and can compound morbidity in pregnant hosts (Christian et al 2010;Avitsur et al 2011;Soydinc et al 2012;Christian 2014;Ingersoll 2017;Vom Steeg and Klein 2017).…”
Section: Pregnancymentioning
confidence: 99%